A hydrodesulfurization catalyst and its preparation method and application

By preparing a hydrogen decarcus catalyst with a large surface area and a large Kong Rong, the problem of fast loss of existing catalysts and poor anti -metal capacity is solved, and the life of the catalyst's usage is extended and the installation cycle is improved.

CN116408115BActive Publication Date: 2025-01-21PETROCHINA CO LTD
View PDF 5 Cites 0 Cited by

Patent Information

Application Number
CN202111671561.0
Authority / Receiving Office
CN · China
Patent Type
Patents(China)
Current Assignee / Owner
Filing Date
2021-12-31
Publication Date
2025-01-21
Estimated Expiration
2041-12-31

AI Technical Summary

Technical Problem

The existing residual oil hydrogenation catalysts have problems such as fast inactivation speed and poor metal resistance in fixed bed or boiling bed industrial devices, resulting in short service life of the catalyst and shortened operation cycle of the device.

Method used

A hydrodesulfurization catalyst with a specific surface area of ​​200 to 320m2/g, a pore volume of 0.7 to 0.95ml/g, and a pore diameter of 20nm to 50nm is used. It is modified by adding phosphorus- and boron-containing pseudo-boehmite to the catalyst. Starch and plant fiber are kneaded, shaped, dried and roasted in an acidic active metal solution to prepare a catalyst with large specific surface area and large pore volume.

Benefits of technology

While maintaining a stable desulfurization effect, this catalyst has better anti -metallic or capacity metal activity and stability, extending the service life of the catalyst, and increasing the operating cycle of the device.

✦ Generated by Eureka AI based on patent content.

Smart Images

  • Figure SMS_1
    Figure SMS_1
  • Figure SMS_2
    Figure SMS_2
  • Figure SMS_3
    Figure SMS_3
Patent Text Reader

Abstract

The present invention discloses a hydrodesulfurization catalyst and its preparation method and application. The specific surface area of ​​the catalyst measured by BET detection method is 200-320m 2 / g, pore volume is 0.7-0.95ml / g, and pores with pore diameters of 20nm-50nm account for 30-50% of the total pore volume. The hydrogen desulfurization catalyst of the present invention has a large specific surface area and a large pore volume, and can have a stable desulfurization effect while also having good anti-metal poisoning or metal-tolerant activity and stability, extending the service life of the catalyst, thereby improving the operation cycle of the device.
Need to check novelty before this filing date? Find Prior Art

Description

Technical Field

[0001] The invention relates to a hydrodesulfurization catalyst and a preparation method and application thereof, which is a technology for hydrodesulfurizing inferior residual oil while improving metal resistance or metal tolerance and extending the service life of the catalyst. Background Art

[0002] At present, the demand for light oil products is huge, and crude oil has a clear trend of becoming heavier and inferior. Therefore, the task of deep processing of heavy oil has become increasingly arduous in recent years. Processing heavy oil, especially heavy residual oil, has become an important task in the oil refining industry. Residue oil hydrogenation technology is an important means of deep processing of residue oil. Among them, fixed bed residue oil hydrogenation technology is the most mature and has been used in domestic industry for many years, and has achieved good economic benefits.

[0003] As we all know, most of the sulfur, nitrogen and almost all of the metals and asphaltene impurities in crude oil remain in the residue. The residue hydrogenation reaction is much more complicated and difficult than the hydrogenation reaction of other distillates, and generally requires a higher hydrogen partial pressure and reaction temperature and a lower volume space velocity. Generally speaking, the residue hydrogenation reaction includes hydrodesulfurization (HDS), hydrodenitrogenation (HDN), hydrodecarbonization (HDCCR), hydrodemetallization (HDM) and other reactions, among which the hydrodemetallization reaction mainly includes hydrodevanadiumization (HDV) and hydrodenickelization (HDNi) reactions. During the operation of the residue hydrogenation unit, the residue hydrogenation catalyst faces a more serious deactivation problem, and its life is generally 1 to 2.5 years. This is mainly because, in addition to the deactivation effect of coking, the deposition of metal (mainly Ni and V) sulfides is also the main factor causing its deactivation. In the fixed bed or fluidized bed residue oil hydrogenation industrial unit, the desulfurization catalyst is loaded behind the demetallization catalyst to undertake part of the demetallization function, and metal will be deposited on the desulfurization catalyst, thus causing the desulfurization catalyst to be deactivated. Most of the metal and sulfur impurities in the residue oil exist in colloids and asphaltene, which are the components with the largest molecular weight and the most complex structure in the petroleum components, with large diffusion resistance and easy to cause pore blockage (causing catalyst deactivation).

[0004] For the hydrogenation reaction of inferior heavy oil or residual oil in fixed bed or ebullating bed, usually multiple catalyst grades are used to remove sulfur, residual carbon and metal from heavy oil or residual oil. For fixed bed or ebullating bed demetallization catalysts, they usually have lower specific surface area and larger pore volume and pore diameter, while desulfurization and residual carbon removal catalysts have larger specific surface area and smaller pore volume. In the fixed bed or ebullating bed residual oil hydrogenation industrial device, the desulfurization catalyst is loaded behind the demetallization catalyst to undertake part of the demetallization function. The desulfurization catalyst currently used in industrial devices has a smaller pore volume and pore diameter, and the metal is deposited at the empty opening of the catalyst pores, causing the catalyst to deactivate faster. Summary of the invention

[0005] In view of the technical defects and technical drawbacks existing in the prior art, the embodiments of the present invention provide a hydrodesulfurization catalyst and a preparation method and application thereof that overcome the above problems or at least partially solve the above problems.

[0006] The present invention provides a hydrodesulfurization catalyst, characterized in that: the specific surface area measured by BET detection method is 200-320m 2 / g, the pore volume is 0.7-0.95 ml / g, and the pores with a pore diameter of 20 nm-50 nm account for 30-50% of the total pore volume.

[0007] Another aspect of the present invention provides a method for preparing the above hydrodesulfurization catalyst, which comprises the following steps:

[0008] Mixing phosphorus-containing and boron-containing pseudo-boehmite in a predetermined ratio to obtain a first mixture;

[0009] adding an extrusion aid and a pore expanding agent to the first mixture to obtain a second mixture;

[0010] adding an acidic active metal solution to the second mixture, kneading, molding, drying, and calcining to obtain the hydrodesulfurization catalyst;

[0011] Wherein, the extrusion aid is modified starch; the pore-enlarging agent is plant fiber; and the acid of the acidic active metal solution is an inorganic acid.

[0012] Another aspect of the present invention provides an application of the hydrodesulfurization catalyst in hydrotreating residual oil, and the application can be hydrodesulfurization treatment of residual oil in a fixed bed or an ebullating bed.

[0013] In another aspect, the present invention provides a method for hydrotreating residual oil, wherein the above-mentioned hydrodesulfurization catalyst is used.

[0014] The embodiments of the present invention achieve at least the following technical effects: the hydrogen desulfurization catalyst of the present invention has a large specific surface area and a large pore volume, and can have a stable desulfurization effect while also having good metal resistance or metal tolerance activity and stability, thereby extending the service life of the catalyst and thus improving the operating cycle of the device.

[0015] Other features and advantages of the present invention will be described in the following description, and partly become apparent from the description, or be understood by practicing the present invention. The purpose and other advantages of the present invention can be realized and obtained by the structure described in the written description, claims, and the like.

[0016] The technical solution of the present invention is further described in detail below through embodiments. DETAILED DESCRIPTION

[0017] The exemplary embodiments of the present disclosure will be described in more detail below. Although exemplary embodiments of the present disclosure are shown in the figure, it should be understood that the present disclosure can be implemented in various forms and should not be limited by the embodiments set forth herein. On the contrary, these embodiments are provided to enable a more thorough understanding of the present disclosure and to fully convey the scope of the present disclosure to those skilled in the art.

[0018] Here, exemplary embodiments will be described in detail. The embodiments described in the following exemplary embodiments do not represent all embodiments consistent with the present invention. Instead, they are merely examples of devices and methods consistent with some aspects of the present invention as detailed in the appended claims.

[0019] First, the technical terms mentioned in each embodiment of the present invention are briefly described as follows:

[0020] Specific surface area: refers to the total area per unit mass of material. The unit is m 2 / g, usually refers to the specific surface area of ​​solid materials, such as powder, fiber, granule, flake, block and other materials.

[0021] Pore ​​volume: also known as pore volume, refers to the total volume of pores per unit mass of porous solids, called pore volume or specific pore volume Vg. This is one of the characteristic values ​​of porous structure adsorbents or catalysts.

[0022] Residue oil: refers to the residual oil obtained by vacuum distillation of crude oil.

[0023] Hydrodesulfurization: refers to the process of converting organic sulfur into easily removable hydrogen sulfide through hydrogenolysis reaction, thereby achieving deep removal.

[0024] Fluidized bed: also known as fluidized bed, is a reactor that uses gas or liquid to pass through a granular solid layer to put the solid particles in a suspended state and carry out a gas-solid phase reaction process or a liquid-solid phase reaction process.

[0025] Fixed bed: refers to a reactor filled with granular solid catalysts or solid reactants to form a stacked bed layer of a certain height. While the gas or liquid material flows through the gaps between the particles through the static fixed bed layer, a heterogeneous reaction process is achieved.

[0026] Anti-metal poisoning ability: Although the metal is deposited in the catalyst pores, the rate of decrease in catalyst activity (desulfurization rate) after metal precipitation of the catalyst prepared according to this method is slower than that of the catalyst prepared by other methods.

[0027] Metal capacity: the amount of metal deposited in the catalyst pores

[0028] BET test method: BET specific surface area test method, this method is named because it is based on the famous BET theory. BET is the abbreviation of three scientists S. Brunauer, P. Emmett and E. Teller. The three scientists derived the multi-molecular layer adsorption formula from the classical statistical theory, that is, the famous BET equation, which has become the theoretical basis of particle surface adsorption science and is widely used in the research of particle surface adsorption performance and data processing of related detection instruments.

[0029] wt%: indicates mass fraction

[0030] The inventors found out when studying the above problems:

[0031] Chinese patent publication No. CN106622314A discloses a high-activity hydrorefining catalyst and a preparation method thereof, wherein water is used as a solvent to prepare a slurry containing silicon-phosphorus-alumina, a boron-containing compound, a VIB group metal compound and a VIII group metal compound are added to the slurry, a filter cake and a filtrate are obtained by filtration, the filtrate is mixed with SB powder and a peptizing agent to obtain a binder, and the binder and the filter cake are successively rolled, formed, dried and calcined to obtain the hydrorefining catalyst. However, the pore volume of this catalyst is small and the deactivation rate is fast.

[0032] Chinese patent publication No. CN96120423 discloses a residual oil hydroprocessing catalyst and a preparation method thereof, which uses γ-Al2O3 as a carrier and supports metal elements of Group VIII and Group VIB, and is characterized in that the pore volume of the catalyst is 0.30-0.60 mL / g and the specific surface area is 120-200 m 2 / g, the average pore size is 9.0-13.0nm, and the pore volume with a pore size of 7.0-13.0nm accounts for more than 80% of the total pore volume. However, the catalyst prepared by this method has a large specific surface area, a small macropore ratio, poor resistance to metal poisoning, and rapid deactivation.

[0033] Chinese patent publication No. CN1417300A discloses a hydrogenation catalyst and a preparation method thereof, wherein the preparation method of the catalyst comprises impregnating a macroporous alumina carrier with a solution containing a metal compound of Group VIB and Group VIII, wherein the preparation method of the alumina carrier comprises extruding a mixture of pseudo-boehmite, acid, water and an extrusion aid, rapidly drying the molded product at 90-300°C within 35 minutes, and calcining the molded product at 600-800°C in a steam-containing atmosphere for at least 0.5 hours, wherein the pore distribution of the obtained alumina carrier is that pores with a diameter of 10-20 nm account for 70-90% of the total pore volume. However, the catalyst prepared by the method has a low pore volume and a low proportion of macropores.

[0034] Chinese patent publication No. CN1103009 discloses a method for preparing a heavy oil hydrodemetallization catalyst carrier, which is made of two aluminum hydroxide precursors with different pore size distributions, carbon black and surfactants as pore expanders, and kneaded, dried and calcined to form a double-pore alumina carrier. However, this method has strict requirements on the precursor alumina raw material, requires the addition of more surfactants, and has a high cost.

[0035] In view of this, in order to achieve the above-mentioned purpose of the invention, the embodiment of the present invention provides a hydrodesulfurization catalyst, which has a large specific surface area and a large pore volume. The specific surface area measured by the BET detection method is 200-320m 2 / g, pore volume is 0.6-0.95ml / g, pores with pore diameters of 20nm-50nm account for 30-50% of the total pore volume. The shape of the hydrodesulfurization catalyst can be changed as required, such as cylindrical, clover-shaped, four-leaf clover, etc. The hydrodesulfurization catalyst can be used as a catalyst for hydrotreating inferior residue oil, especially a fixed bed or ebullient bed residue oil hydrosulfurization catalyst.

[0036] The hydrodesulfurization catalyst in this embodiment has a large pore volume, which is conducive to the passage of impurity-containing macromolecules, the reaction inside the catalyst pores, and the increase of demetallization capacity; by maintaining a large specific surface area, it is conducive to the desulfurization activity. In a fixed bed or boiling bed residual oil hydrogenation industrial device, after the inferior heavy oil passes through the demetallization catalyst bed, the asphaltene and colloid react and reduce in size. Therefore, a residual oil hydrodesulfurization catalyst with a large specific surface and large pore volume is prepared, and the content of pores with a pore size of 20 to 50 nm is appropriately increased. While maintaining the desulfurization activity, it is easy for the asphaltene and colloid after the reaction of the demetallization catalyst bed to enter the pores to react, slowing down the deactivation rate of the desulfurization catalyst, extending the service life of the catalyst, and increasing the operation cycle of the device.

[0037] The preparation method of the above-mentioned hydrodesulfurization catalyst may include the following steps: mixing phosphorus-containing and boron-containing pseudo-boehmite in a predetermined ratio to obtain a first mixture; adding an extrusion aid and a pore expander to the first mixture to obtain a second mixture; adding an acidic active metal solution to the second mixture, kneading, molding, drying, and roasting to obtain the hydrodesulfurization catalyst; wherein the extrusion aid is modified starch; the pore expander is plant fiber; and the acid of the acidic active metal solution is an inorganic acid.

[0038] Specifically, the above-mentioned pseudo-boehmite is respectively phosphorus-containing pseudo-boehmite and boron-containing pseudo-boehmite, wherein the phosphorus content in the phosphorus-containing pseudo-boehmite as oxide can be 3wt%-7wt% of the content of the pseudo-boehmite; the boron content in the boron-containing pseudo-boehmite as oxide can be 2wt%-5wt% of the content of the pseudo-boehmite; the mixing mass ratio of the phosphorus-containing pseudo-boehmite and the boron-containing pseudo-boehmite can be 4:1 to 1:4, preferably 3:1 to 1:3; the specific surface area of ​​the phosphorus-containing pseudo-boehmite is ≥400m 2 / g, pore volume ≥1.05ml / g; specific surface area of ​​boron-containing pseudo-boehmite ≥350m 2 / g, pore volume ≥1.15ml / g.

[0039] The extrusion aid may be modified starch, and the mass content of the modified starch may be 1wt% to 6wt%, preferably 2wt to 4wt%, of the alumina content in the first mixture.

[0040] The plant fiber can be one or more of cotton fiber, bamboo fiber, and leaf fiber, and the added amount can be 0.5wt~6wt% of the aluminum oxide content in the first mixture, preferably 2wt~4wt%; the particle size of the plant fiber is 40~100 mesh.

[0041] The active metal in the above-mentioned acidic active metal solution may be a hydrogenation active metal component with a metal of Group VIB and / or Group VIII. The metal of Group VIB may be at least one of Mo and W. The metal of Group VIII may be at least one of Ni and Co. The Mo salt may be one or more of ammonium molybdate, sodium phosphomolybdate, ammonium phosphomolybdate, and molybdenum oxide; the Ni salt may be one or more of nickel nitrate, nickel acetate, and basic nickel carbonate. In terms of oxide, molybdenum or tungsten may account for 8wt% to 20wt% of the total mass of the hydrodesulfurization catalyst, and nickel or cobalt may account for 2wt% to 5wt% of the total mass of the hydrodesulfurization catalyst. The inorganic acid in the above-mentioned acidic active metal solution may be one or more of phosphoric acid, nitric acid, and hydrochloric acid.

[0042] The above-mentioned forming process can be carried out by using a screw extruder, and its extrusion pressure can be 15-50 MPa. The drying temperature of the above-mentioned drying process can be 100-200°C, and the calcination temperature of the above-mentioned roasting process can be 500-900°C, preferably 750-850°C, and the roasting time can be 3-6 hours.

[0043] The preparation method provided in this embodiment first combines the characteristics of high specific surface area of ​​phosphorus-containing pseudo-boehmite and high pore volume of boron-containing pseudo-boehmite, adds modified starch and plant fiber, and the modified starch acts as a lubricant and is adsorbed and wrapped around the plant fiber, which can reduce the kneading pressure and reduce the effect of the subsequent addition of acid in the acidic metal solution on the pore expansion of the selected particle size plant fiber, thereby directionally expanding the proportion of pores with a pore size of 20 to 40 nm. Maintaining a large specific surface area can provide sufficient reactive sites, and the increase in the proportion of macropores helps asphaltene and colloid macromolecules to react inside the catalyst pores, inhibits coking and metal deposition poisoning caused by blocking the pores, overcomes the shortcomings of poor metal resistance and rapid deactivation in the prior art, slows down the deactivation rate of the desulfurization catalyst, prolongs the service life of the catalyst, and increases the operating cycle of the device.

[0044] In order to further verify the above technical effects, the following experimental data are provided:

[0045] Example 1

[0046] Weigh 250 g of phosphorus-containing pseudo-boehmite dry glue powder (specific surface area 412 m 2 / g, pore volume 1.10ml / g), weigh 250g of boron-containing pseudo-boehmite dry glue powder (specific surface area 350m 2 / g, pore volume 1.15ml / g), equivalent to a ratio of 1:1, after mixing, add 3g modified starch (i.e. 1wt%) and 20g cotton fiber (40 mesh, 6wt%), mix evenly; add 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add water to make up to 500ml; then extrude into a four-leaf clover shape with a particle size of 1.4-1.6mm on a front extrusion single screw extruder, extrusion pressure 15MPa, dry at 100℃ for 3 hours, and then roast at 700℃ for 6 hours to obtain catalyst A1. Catalyst properties are shown in Table 1.

[0047] Example 2

[0048] Weigh 250 g of phosphorus-containing pseudo-boehmite dry powder (specific surface area 400 m 2 / g, pore volume 1.05ml / g), weigh 250g of boron-containing pseudo-boehmite dry glue powder (specific surface area 360m 2 / g, pore volume 1.20ml / g), equivalent to a ratio of 1:1, after mixing, add 20g modified starch (i.e. 6wt%) and 15g bamboo fiber (100 mesh, 5wt%), mix evenly; add 500ml Mo-Ni-P solution (the catalyst contains MoO310wt%, NiO 5wt%) and knead, wherein the configuration of Mo-Ni-H3PO4 solution is as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add water to make up to 500ml; then extrude into a clover shape with a particle size of 1.6mm on a front extrusion single screw extruder, extrusion pressure 40MPa, dry at 200℃ for 3 hours, and then calcine at 900℃ for 3 hours to obtain catalyst A2. Catalyst properties are shown in Table 1.

[0049] Example 3

[0050] Weigh 250 g of phosphorus-containing pseudo-boehmite dry powder (specific surface area 400 m 2 / g, pore volume 1.05ml / g), weigh 250g of boron-containing pseudo-boehmite dry glue powder (specific surface area 350m 2 / g, pore volume 1.15ml / g), equivalent to a ratio of 1:1, after mixing, add 20g modified starch (i.e. 6wt%) and 10g leaf fiber (i.e. 3wt%), mix evenly; add 500ml Mo-Ni-P solution (the catalyst contains MoO310wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 100ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add water to make up to 500ml; then extrude into a cylindrical shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 25MPa, dry at 120℃ for 3 hours, and then calcine at 800℃ for 5 hours to obtain catalyst A3. Catalyst properties are shown in Table 1.

[0051] Example 4

[0052] Weigh 375 g of phosphorus-containing pseudo-boehmite dry glue powder (specific surface area 400 m 2 / g, pore volume 1.05ml / g), weigh 125g of boron-containing pseudo-boehmite dry glue powder (specific surface area 350m 2 / g, pore volume 1.15ml / g), equivalent to a ratio of 3:1, after mixing, add 10g modified starch (i.e. 3wt%) and 20g cotton fiber (i.e. 6wt%), mix evenly; add 500ml Mo-Ni-P solution (the catalyst contains MoO310wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add water to make up to 500ml; then extrude into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, dry at 120℃ for 3 hours, and then roast at 850℃ for 5 hours to obtain catalyst A4. Catalyst properties are shown in Table 1.

[0053] Example 5

[0054] Weigh 125 g of phosphorus-containing pseudo-boehmite dry glue powder (specific surface area 400 m 2 / g, pore volume 1.05ml / g), weigh 375g of boron-containing pseudo-boehmite dry glue powder (specific surface area 350m 2 / g, pore volume 1.15ml / g), equivalent to a ratio of 1:3, 10g modified starch (i.e. 3wt%) and 20g cotton fiber (i.e. 6wt%) were added and mixed evenly; 500ml Mo-Ni-P solution (the catalyst contains MoO3 10wt%, NiO 5wt%) was added and kneaded, wherein the Mo-Ni-H3PO4 solution was configured as follows: 50g molybdenum trioxide was added to 200ml H3PO4 solution and stirred to dissolve completely, 32g basic nickel carbonate was added and stirred until completely dissolved, and water was added to make up to 500ml; then it was extruded into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, the extrusion pressure was 15MPa, and it was dried at 120℃ for 3 hours, and then calcined at 900℃ for 5 hours to obtain catalyst A5. The catalyst properties are shown in Table 1.

[0055] Example 6

[0056] Weigh 250 g of phosphorus-containing pseudo-boehmite dry powder (specific surface area 400 m 2 / g, pore volume 1.05ml / g), weigh 250g of boron-containing pseudo-boehmite dry glue powder (specific surface area 350m 2 / g, pore volume 1.15ml / g), equivalent to a ratio of 1:1, after mixing, add 20g modified starch (i.e. 6wt%) and 5g leaf fiber, 5g bamboo fiber, 10g cotton fiber, mix evenly; add 500ml Mo-Ni-P solution (the catalyst contains MoO310wt%, NiO 5wt%) and knead, wherein the Mo-Ni-H3PO4 solution is configured as follows: add 50g molybdenum trioxide to 200ml H3PO4 solution and stir to dissolve completely, add 32g basic nickel carbonate and stir until completely dissolved, add water to make up to 500ml; then extrude into a cylindrical shape with a diameter of 1.6mm on a front extrusion single screw extruder, extrusion pressure 25MPa, dry at 120℃ for 3 hours, and then roast at 800℃ for 5 hours to obtain catalyst A6. Catalyst properties are shown in Table 1.

[0057] Comparative Example 1

[0058] According to the method described in Chinese patent CN106622314 A, 25g of molybdenum trioxide and 16g of basic nickel carbonate were added to the slurry containing silicon-phosphorus-alumina, filtered to obtain a filter cake and a filtrate, the filtrate was mixed with SB powder and a peptizing agent to obtain an adhesive, the adhesive and the filter cake were extruded into a clover shape with a diameter of 1.6mm on a front extrusion single screw extruder, dried at 120°C for 3 hours, and then calcined at 800°C for 5 hours to obtain catalyst B1. The catalyst properties are shown in Table 1.

[0059] Comparative Example 2

[0060] According to the method described in Chinese patent CN96120423, an alumina carrier was prepared and impregnated with 150 ml of Mo-Ni-P solution (containing MoO3 10 wt %, NiO 5 wt %), wherein the Mo-Ni-H3PO4 solution was prepared as follows: 25 g of molybdenum trioxide was added to 100 ml of H3PO4 solution and stirred to dissolve completely, then 16 g of basic nickel carbonate was added and stirred until completely dissolved, and water was added to make up to 150 ml; after the spray immersion was completed, the excess solution was filtered off, the solution was dried at 120°C for 3 hours, and then calcined at 500°C for 4 hours to obtain catalyst B2.

[0061] Comparative Example 3

[0062] According to the method described in Chinese patent CN1417300A, 300g of pseudo-boehmite was weighed, mixed evenly with 3.9g of 65wt% nitric acid, 3g of sesbania powder and 120g of deionized water, and extruded into 1.6mm Sanye grass shape on an extruder. The mixture was dried at 110°C by forced air. After drying, 100% water vapor was introduced into the dried molded product at 750°C and calcined for 5 hours to obtain a carrier. 150ml of Mo-Ni-P solution (containing MoO3 10wt%, NiO 3.5wt%) was added to the obtained product for impregnation, wherein the Mo-Ni-H3PO4 solution was prepared as follows: 25g of molybdenum trioxide was added to 100ml of H3PO4 solution and stirred to dissolve completely, then 16g of basic nickel carbonate was added and stirred until completely dissolved, and water was added to make up to 150ml. After spray impregnation, the excess solution was filtered off, dried at 120°C for 3 hours, and then calcined at 500°C for 4 hours to obtain catalyst B.

[0063] Table 1 Catalyst properties

[0064]

[0065] The results in Table 1 show that, compared with the comparative example, the specific surface area and pore volume of the catalyst prepared by the method described in the embodiment of the present invention are greater than those of the comparative example, and the content of pores with a pore diameter of 20 to 50 nm is significantly higher than that of the comparative example.

[0066] The activity stability of the catalyst in Table 1 was evaluated. The evaluation conditions are shown in Table 2, and the evaluation results are shown in Table 3.

[0067] Table 2 Catalyst evaluation conditions

[0068] Raw oil properties Middle East Residue <![CDATA[Density (20 °C) / g·cm -3 > 0.987 Sulfur, wt% 3.6 <![CDATA[(Ni+V),μg.g -1 ]]> 80 Process conditions Reaction temperature, °C 385 Hydrogen partial pressure, MPa 16 <![CDATA[Space velocity, h -1 > 0.4 Hydrogen / Oil Ratio 700

[0069] Table 3 Catalyst demetallization rate

[0070]

[0071] Table 4 Catalyst desulfurization rate

[0072]

[0073]

[0074] It can be seen from the data in Table 3 and Table 4 that the catalysts of the embodiments of the present invention have better desulfurization activity stability and better demetallization activity stability.

[0075] Finally, it should be noted that the above embodiments are only used to illustrate the technical solutions of the present invention, rather than to limit it. Although the present invention has been described in detail with reference to the aforementioned embodiments, those skilled in the art should understand that they can still modify the technical solutions described in the aforementioned embodiments, or make equivalent replacements for some of the technical features therein. However, these modifications or replacements do not deviate the essence of the corresponding technical solutions from the spirit and scope of the technical solutions of the embodiments of the present invention.

Claims

1. A method for preparing a hydrodesulfurization catalyst, wherein: The specific surface area of ​​the hydrodesulfurization catalyst measured by the BET detection method is 200 to 320 m 2 / g, the pore volume is 0.7-0.95mL / g, and the pores with a pore diameter of 20nm-50nm account for 30%-50% of the total pore volume, characterized in that the preparation method comprises the following steps: Mixing the phosphorus-containing pseudo-boehmite and the boron-containing pseudo-boehmite in a predetermined ratio to obtain a first mixture; adding an extrusion aid and a pore expanding agent to the first mixture to obtain a second mixture; adding an acid-containing active metal solution to the second mixture, kneading, molding, drying, and calcining to obtain the hydrodesulfurization catalyst; Wherein, the extrusion aid is modified starch; the pore-enlarging agent is plant fiber; the acid in the acid-containing active metal solution is an inorganic acid; The plant fiber is one or more of cotton fiber, bamboo fiber, and leaf fiber; The amount of the plant fiber added is 3wt% to 6wt% of the alumina content in the first mixture; The particle size of the plant fiber is 40 to 100 meshes; The mixing mass ratio of the phosphorus-containing pseudo-boehmite to the boron-containing pseudo-boehmite is 4:1 to 1:

4.

2. The preparation method according to claim 1, characterized in that: The specific surface area of ​​the phosphorus-containing pseudo-boehmite is ≥400m 2 / g, pore volume ≥1.05mL / g; The specific surface area of ​​the boron-containing pseudo-boehmite is ≥350m 2 / g, pore volume ≥1.15mL / g.

3. The preparation method according to claim 2, characterized in that: The mixing mass ratio of the phosphorus-containing pseudo-boehmite to the boron-containing pseudo-boehmite is 3:1 to 1:

3.

4. The preparation method according to claim 1, characterized in that: The mass content of the modified starch is 1wt% to 6wt% of the aluminum oxide content in the first mixture.

5. The preparation method according to claim 1, characterized in that: The active metal in the acid-containing active metal solution includes Group VIB and / or Group VIII metals as hydrogenation active metal components.

6. The preparation method according to claim 5, characterized in that: The VIB group metal is Mo; and the VIII group metal is Ni.

7. The preparation method according to claim 1, characterized in that: The inorganic acid is phosphoric acid.

8. The preparation method according to claim 1, characterized in that: The molding is carried out by using a screw extruder, and the extrusion pressure is 15-40 MPa.

9. The preparation method according to claim 1, characterized in that: The drying temperature is 100-200°C.

10. The preparation method according to claim 1, characterized in that: The calcination temperature is 700-900° C., and the calcination time is 3-6 hours.

11. The preparation method according to claim 10, characterized in that: The calcination temperature is 750-850°C.

12. The preparation method according to claim 1, characterized in that: The shape of the hydrodesulfurization catalyst is cylindrical, three-leaf clover or four-leaf clover.

13. Use of the hydrodesulfurization catalyst obtained by the preparation method according to any one of claims 1 to 12 in hydrotreating residual oil.

14. The use according to claim 13, characterized in that The hydroprocessing of the residual oil includes: performing hydrodesulfurization treatment on the residual oil in a fixed bed or a fluidized bed.

Citation Information

Patent Citations

  • Catalyzer for hydrotreating residuum and its prepn. method

    CN1053458C

  • High-activity hydrofining catalyst and preparation method thereof

    CN106622314A

  • Hydrogenating and demetalization catalyst and its prepn

    CN1417300A

  • Coal tar hydrogenation pretreatment catalyst and preparation method thereof

    CN111617789A

  • Demetalating and desulfurizing hydrocatalyst and its preparing process

    CN1351115A